Readiness of students towards "Pentaksiran Tingkatan Tiga" (PT3) (Form Three Assessment) / Fatima Sabbir - Sabbir, Fatima (2015)
The implementation of "Pentaksiran Tingkatan Tiga" (PT3) (Form Three Assessment) was proposed in an attempt to replace the Lower Secondary Assessment {Penilaian Menengah Rendah) examination. The change of the assessment system was only made known to the students in April 2014. As the first cohort of PT3, the form three students had very little time to be familiarised to the new assessment system. However, relatively little is known about the readiness level of the students towards PT3. Therefore, a study was conducted to investigate the level of readiness of the students towards PT3. Students' readiness in this study was limited to three main aspects, namely; students' understanding and knowledge, students' readiness and students' perceived view towards PT3. A descriptive and correlation research was employed to examine the students' level of readiness. A total of 746 form three students from four secondary schools in Klang, Selangor, were involved in the study. An adapted questionnaire was used to collect the study data. Convenience sampling was employed in determining the sample size of the study. The study indicated that the respondents have high level of readiness towards PT3. On the other hand, the findings revealed the respondents possess moderate level of understanding and perceived view towards PT3. The findings showed that there is a weak correlation between students' readiness level and PT3 English trial marks (r = .277**), a weak correlation between students' readiness level and understanding of PT3 (r = .433**) and a weak correlation between students' readiness level and perceived view of PT3 (r = .349**). Future research should use larger sample size to obtain broader perspective of the level of readiness of students as well as teachers towards PT3.